Diagnostic and Prognostic Potential of Retinal Biomarkers in Early On-Set Alzheimer's Disease - Shariflou, Sahar; Georgevsky, Dana; Mansour, Hussein; Rezaeian, Mahdie; Hosseini, Nafiseh; Gani, Fathima; Gupta, Vivek; Braidy, Nady; Mojtaba Golzan, S. (Current Alzheimer Research, 2017)
Objective: Accumulating evidence suggests that the eye can be used in the assessment of early on-set Alzheimer's disease (AD). The eye offers a natural window to the brain through the retina. The retina and brain share common developmental origins and patho-physiological origins and mechanisms, having been sequestered from it during early development, but retaining its connections with the brain via the optic nerve. Therefore, it is well understood that neurological abnormalities have a direct profound impact on the retina. Recent studies suggest an array of physiological and pathological changes in the retina in dementia and specifically in AD. There are also reports on imaging the two hallmark proteins of the disease, extracellular amyloid beta peptides and intracellular hyper phosphorylated tau protein, as a proxy to neuroimaging. Results: In this review, we summarise retinal structural, functional and vascular changes reported to be associated with AD. We also review techniques employed to image these two major hall mark proteins of AD and their relevance for early detection of AD.
Keywords: tau